SOME CLINICAL AND IMMUNOLOGICAL ASPECTS OF FREQUENT SICK CHILDREN WITH HYPOTROPHY - G.S. MAMADJANOVA; Z.K. UMAROVA; M.D. YODGOROVA; M.P. NOSIROVA (Avicenna Tajik State Medical University, 2017)
Objective: To study some clinical and immunological aspects of frequent sick children (FSC) with hypotrophy Methods: 60 FSC with hypotrophy were observed. All children were divided according to the degree and severity of the disease: light - 20, average - 20, heavy - 20. The control group included 20 children. The age composition ranged from 2 months to 2 years. Methods of examination included: clinical observation, laboratory and immunological studies: quantification of leukocytes and lymphocytes. The number of lymphocytes and their subpopulations was determined using monoclonal antibodies to the differential antigens CD3, CD4, CD8, CD20, CD95, CD16, CD32. Results: In FSC with hypotrophy of light severity showed T-cells, and their subpopulation and Ig A, Ig M, and Ig G values tended to decrease in comparison with the control group. In most cases, they had uncomplicated respiratory infections, and there were no statistically reliable deviations. In FSC with hypotrophy of average severity, there was a noticeable and reliable decrease in both cellular and humoral immunity. The indices in patients with heavy severity of disease in comparison with those, in patient's groups I and II differed even with a higher significant difference. The effectiveness of immunomodulatory therapy has been noted. Conclusion: Immunomodulatory therapy in combination with basic therapy led to a significant increase in the indices of cellular and humoral immunity in dynamics. The evidence of this was a significant decrease in intercurrent diseases in FSC with hypotrophy.